Legal Implications of Covert CCTV Surveillance: Liability for Offenders and Obligations of Premises Owners - Hana Yunita Makhfudotin; Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2024)
This study employs a normative juridical approach, specifically utilizing the statutory method, to analyze the legal repercussions of clandestine CCTV surveillance. Drawing from primary legal sources such as Law Number 11 of 2008 concerning Information and Electronic Transactions, Law Number 27 of 2022 concerning Protection of Personal Data, Law Number 44 of 2008 concerning Pornography, and the Criminal Code, this research delves into the ethical and legal dimensions surrounding the installation of covert cameras in public and private spaces. Results indicate that clandestine CCTV recording infringes upon individual privacy and security rights, posing serious ethical and legal challenges. Moreover, this study elucidates the responsibilities of property owners where such surveillance occurs. The implications underscore the imperative for stringent legal measures to safeguard personal privacy and uphold ethical standards in surveillance practices. Highlights : Hidden CCTV installations breach individual privacy and security rights, raising significant legal concerns. Analysis of primary legal sources reveals the complex interplay between electronic transactions laws, personal data protection regulations, and statutes addressing pornography and criminal offenses. Property owners bear responsibility in ensuring ethical and lawful surveillance practices within their premises, necessitating clear legal guidelines and enforcement mechanisms. Keywords: CCTV surveillance, legal consequences, privacy rights, statutory approach, ethical standards.